Molecular assemblies and pharmacology of cerebellar GABA A receptors - Chang Sun; Jennifer N. Jahncke; Kevin M. Wright; Eric Gouaux (Proceedings of the National Academy of Sciences, 2026)
GABA A receptors (GABA A Rs) mediate fast inhibitory neurotransmission in the brain and are assembled from 19 subunit isoforms into multiple pentameric assemblies. Although α1-containing GABA A Rs are broadly expressed and are pharmacologically important, the molecular diversity of native α1-based assemblies in specific brain regions remains incompletely understood. Here, we use immunofluorescence, mass spectrometry, and cryogenic electron microscopy (cryo-EM) to characterize the spatial distribution, subunit composition, and structural architecture of native α1-containing GABA A Rs in the rat cerebellum. Confocal microscopy reveals robust colocalization of α1 and γ2 subunits across cerebellar layers, including prominent labeling at glomerular synapses. Biochemical purification and proteomic analysis identify a range of α, β, and γ subunits, along with abundant α6 and δ subunits. Using cryo-EM and automated subunit identification, we resolve eight α1-containing receptor assemblies, including the first structure of α6-containing receptors. We further determine the binding mode of the α6-selective pyrazoloquinolinone modulator PZ-II-029 at the α + /γ – interface, showing ligand-induced expansion of the entire extracellular domain (ECD). Together, our study defines the structure and subunit composition of the α1-containing cerebellar GABA A Rs and elaborates the molecular interactions between native receptors and pyrazoloquinolinone, thereby laying the groundwork for brain region and subunit-specific pharmacology.